THE METHOD OF DETERMINING THE CRACK IN REINFORCED CONCRETE T-BEAM PROFILE - Luchko, Y. Y.; Ivanyk, Ye. H. (Science and Transport Progress, 2009)
In the paper the method for determination of the width of crack opening of the ferro-concrete beam of the teeform profile in dependence on the shelf and wall geometrical sizes, external load and reinforcement percent is described.